2017
DOI: 10.1007/s10549-017-4216-6
|View full text |Cite
|
Sign up to set email alerts
|

ΔNp63 activates EGFR signaling to induce loss of adhesion in triple-negative basal-like breast cancer cells

Abstract: These data identify EGFR as a major target for ΔNp63 regulation that influences cancer cell adhesion in basal-like triple-negative breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 54 publications
4
21
0
Order By: Relevance
“…At first glance this is surprising due to the previously assumed dominant negative role of this transactivation domain-lacking isoform (52). Interestingly, our report is joined by other studies demonstrating a role of deltaNp63 as a transcriptional activator (53)(54)(55)(56)(57)(58). For example, the viral oncogene protein BamHI-A rightward frame 1 (BARF1) was shown to be exclusively transactivated by deltaNp63 and not p53 or TAp63 in epithelial tumors (54).…”
Section: Discussionsupporting
confidence: 48%
“…At first glance this is surprising due to the previously assumed dominant negative role of this transactivation domain-lacking isoform (52). Interestingly, our report is joined by other studies demonstrating a role of deltaNp63 as a transcriptional activator (53)(54)(55)(56)(57)(58). For example, the viral oncogene protein BamHI-A rightward frame 1 (BARF1) was shown to be exclusively transactivated by deltaNp63 and not p53 or TAp63 in epithelial tumors (54).…”
Section: Discussionsupporting
confidence: 48%
“…Our own work showed that p63 controls TGF-β signaling in tumors via additional upstream miRs, thereby suppressing KSRP and miR-198 and promoting metastatic tumor dissemination, all in keeping with the wound-healing response delineated by Sundaram et al (2017) (Rodriguez Calleja et al, 2016. In addition, reciprocal regulatory interactions have been demonstrated between p63 and EGFR signaling in HNS CC and breast cancer, which provides another point of connection with the new findings (Holcakova et al, 2017). Although the involvement of SOX2 and p63 in this context may not be immedi-ately therapeutically actionable, emerging data on control of the epigenome by these central transcription factors alludes to the potential viability of future epigenetic therapy approaches for refractory HNS CC (Alexandrova et al, 2013).…”
supporting
confidence: 66%
“…In particular, ΔNp63α is known to regulate EMT in primary human keratinocytes and in HNC cell lines in a TGFβ-dependent manner 33 , 34 and its downregulation reduces EGFR expression in triple-negative basal-like breast cancer cells and in pancreatic cancer cells promoting cell growth and chemoresistance. 50 , 51 Thus, we showed for the first time that p63 silencing reduced EGFR expression in both HPV-positive and HPV-negative cell lines, showing also that SAHA-mediated inhibition of EGFR greatly correlates with ΔNp63α inhibition. Taken together, these data suggest that SAHA-mediated EGFR downregulation is p63-dependent.…”
Section: Discussionmentioning
confidence: 60%
“…Recently, it has been shown that silencing endogenous ΔNp63α reduces EGFR expression in triple-negative basal-like breast cancer cells and in pancreatic cancer cells promoting cell growth and chemoresistance. 50 , 51 We thus assessed EGFR expression in HPV-positive and HPV-negative HNC cell lines upon p63 knockdown. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%